STEM LEARNING IN MATERIAL OF TEMPERATURE AND ITS CHANGE TO IMPROVE SCIENTIFIC LITERACY OF JUNIOR HIGH SCHOOL - Khaeroningtyas, N.; Permanasari, A.; Hamidah, I. (Jurnal Pendidikan IPA Indonesia, 2016)
This research aims to determine the improvement of studentsâ scientific literacy after STEM (Science, Technology, Engineering, and Mathematics) learning using 6E Learning by DesignTM Model on temperature and its changes material. The research was conducted in SMP Negeri (State Junior High School) 1 Bumiayu in the academic year 2015/2016. The method used was quasi-experimental design with The Matching Only - pretest posttest control group design. This study used two group of experiment group of students who learned the material with STEM learning using 6E Learning by DesignTM, while the control group students learned with non-STEM learning. The analysis showed that the students scientific literacy in experiment group is better than control group. The conclusion that can be drawn is STEM learning using 6E Learning by DesignTM on temperature and its changes material can improve studentsâ scientific literacy.